1996
DOI: 10.1111/j.1472-8206.1996.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of the electrogenic Na+/K+ pump on the mechanical activity in the rat uterus

Abstract: The effects of ouabain and K(+)-free solution were studied in estrogen-primed rat uterine strips under resting tone or repeatedly stimulated with KCl, acetylcholine or oxytocin applied for 20 minutes at 60 minute intervals. These effects were compared with those of the K+ channel opener cromakalim. In preparations under resting tone, ouabain (0.1 mM and 0.3 mM) induced rhythmic contractions which disappeared after 20-30 minutes whereas at a higher concentration (1 mM) it evoked a rapid, phasic response followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Ouabain, K+-free and low Na+ (25 mM) solutions induced biphasic responses composed of an early rapid (ouabain and K+-free solution) or slower developed (low Na+ solution) transient contraction followed by a small sustained contraction. Ouabain and K+-free solution have been shown to inhibit the electrogenic Na+ pump and to induce contractions in various types of smooth muscles (Lamb et al, 1988;Tsuchiya et al, 1990;Ausina et al, 1996). A decrease in the [Na+],,/[Na+Ii ratio by reduction of [Na+I0 also results in tension development and the relative rate of contraction is inversely related to "a+], (Savineau et al, 1987;Sat0 and Aoki, 1991).…”
Section: Kci (% Ach) O U a (% Ach) K-free (% A Ch)mentioning
confidence: 99%
“…Ouabain, K+-free and low Na+ (25 mM) solutions induced biphasic responses composed of an early rapid (ouabain and K+-free solution) or slower developed (low Na+ solution) transient contraction followed by a small sustained contraction. Ouabain and K+-free solution have been shown to inhibit the electrogenic Na+ pump and to induce contractions in various types of smooth muscles (Lamb et al, 1988;Tsuchiya et al, 1990;Ausina et al, 1996). A decrease in the [Na+],,/[Na+Ii ratio by reduction of [Na+I0 also results in tension development and the relative rate of contraction is inversely related to "a+], (Savineau et al, 1987;Sat0 and Aoki, 1991).…”
Section: Kci (% Ach) O U a (% Ach) K-free (% A Ch)mentioning
confidence: 99%
“…Data from a previous study on rat myometrial preparations showed that 100–300 μ mol/L ouabain induces a significant increase in rhythmic contractions and no increase in resting force (Ausina et al. ). These findings are in broad agreement with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Different concentrations of ouabain can therefore be used as a way to interrogate and functionally separate the a isoforms in a tissue (Monteith and Blaustein 1998). Ouabain at different concentrations has been reported indirectly to increase Ca 2+ signaling in myometrium but no measurements of intracellular Ca 2+ were made, and the very high concentrations of ouabain used were not designed to allow the effects on the different isoforms to be tested (Ausina et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Відомо, що уабаїн пригнічує ацетилхолінові скорочення вісцеральних гладень-ких м'язів, причому спостерігається переважне інгібування фазного компонента скоротливих відповідей [1,34]. Дослідженнями S. Usune і колег встановлено, що така дія уабаїну залежить від внутрішньоклітинної концентрації іонів Na + і усува-ється за наявності блокатора Na 2+ і супроводжується зниженням напруження м'язів за умови тонічного ско-рочення, отримане нами відносне збільшення тонічного компонента ацетилхоліно-вих скорочень за попереднього блокування натрієвої помпи уабаїном може бути пов'язане з пригніченням витоку іонів K + через ВК Са -канали.…”
Section: модуляція викликаних Kunclassified